Surveillance of hepatocellular carcinoma by medical imaging - Dietrich, Christoph F.; Teufel, Andreas (Quantitative imaging in medicine and surgery, 2019)
Effective treatments for early-stage hepatocellular carcinoma (HCC) have provided the rationale for HCC surveillance since detection of the disease at an early stage is associated with more favorable outcome. In a prospective multi-institutional diagnostic study, Park et al . (1) evaluated the added value of (perfluorobutane) contrast-enhanced ultrasound (CEUS) when combined with conventional B-mode ultrasound (US) as an HCC surveillance tool in participants with liver cirrhosis using a single arm, intraindividual comparison study design.
Accepted for publication Oct 05, 2019
Gesehen am 07.02.2020